PORTRAIT OF THE BEGINNIG OF A TEACHER CAREER - Fonsaca Ruy, Fabiana Alessandra [UNESP]; Chaluh, Laura Noemi [UNESP] (Univ Metodista Piracicaba-unimep, 2019)
This article is part of a research that aimed to understand the experiences lived by teachers in the beginning of their career. To achieve this, a group was formed with beginner teachers participating. In the group, with monthly meetings, we developed proposals articulated to the discussions related to teaching. Some questions that guided this study were the following: What are the relationships that the teacher starting a career establish in the school? What is the importance of these relationships and how they mark the teacher's daily actions in school life? How do the experience lived affect and constitute the teacher being ? How does the school receive and follow these teachers in the process of insertion in school? This is a narrative research of lived experiences (LIMA; GERALDI; GERALDI, 2015) and the production of data was based on the Indicative Paradigm (GINZBURG, 1989). In this artic le, we g ive visibility to the experiences of one of the beginner teachers using one of her written productions, due to the specificities and extent of her experiences in this phase of her career, and we establish relationships with the literature approaches on this subject. This work suggests the need for policies for welcoming new teachers.
Keywords: BEGINNER TEACHERS; TEACHER TRAINING; NARRATIVE SEARCH